2021
DOI: 10.3390/pharmaceutics13121987
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of miR-345 and Its Effective Delivery as a Potential Therapeutic Candidate in Pancreatic Cancer and Other Cancers

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with high mortality, poor prognosis, and palliative treatments, due to the rapid upregulation of alternative compensatory pathways and desmoplastic reaction. miRNAs, small non-coding RNAs, have been recently identified as key players regulating cancer pathogenesis. Dysregulated miRNAs are associated with molecular pathways involved in tumor development, metastasis, and chemoresistance in PDAC, as well as other cancers. Targeted treatment strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 119 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…In mild stage miR345 is highly express. miR345 is the microRNA that targeting the expression of tumour suppressor gene, activities of peroxisome and ATP generation (13). In moderate stage, miR347 and miR512 is highly express in blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…In mild stage miR345 is highly express. miR345 is the microRNA that targeting the expression of tumour suppressor gene, activities of peroxisome and ATP generation (13). In moderate stage, miR347 and miR512 is highly express in blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that the disrupted expression of these small molecules can contribute to the onset of other longer-term diseases. The dysregulation of the host miRNA range that modulates multiple gene expressions can influence cancer development, either directly or indirectly [ 43 ]. In fact, different miRNAs can function as oncogenes or tumor-suppressor genes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggested that SNHG15 could function as miRNA sponges to inhibit the expression of miRNAs (45). miRNAs play important roles in cell signaling, cell survival, DNA methylation, and invasiveness (46). MiR-345-5p has been shown to regulate the expression of human multidrug resistanceassociated protein 1 (ABCC1/MRP1), suggesting that deregulation of miRNA expression is linked to the cisplatin resistant phenotype (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play important roles in cell signaling, cell survival, DNA methylation, and invasiveness (46). MiR-345-5p has been shown to regulate the expression of human multidrug resistanceassociated protein 1 (ABCC1/MRP1), suggesting that deregulation of miRNA expression is linked to the cisplatin resistant phenotype (46)(47)(48). In this study, we found that the effect of SNHG15 knockdown was restored by the inhibition of miR-345-5p, suggesting that overexpression miR-345-5p might play a key role in tumor suppression and cisplatin sensitivity.…”
Section: Discussionmentioning
confidence: 99%